Risk Factor of Urolithiasis in Redisari Village, Rowokele Sub Ditrict, Kebumen District - Sarwono Sarwono; Onny Setiani; Nurjazuli Nurjazuli (Public Health Department, Universitas Islam Negeri Alauddin Makassar, 2017)
The biggest case on urinary clinic is urolithiasis. Based on the medical record data of Kebumen Hospital, there were 91 patients, consist of 65 men (71.43 %) and 26 women (28.57 %) who treated as urolithiasis patiens in 2013. Urinary tract stone formation is influenced by intrinsic and extrinsic factors. Purpose : To analyze the risk factors of urolithiasis in Redisari village, Rowokele, Kebumen district.This was an observational study with cross sectional design. The sample were 80 people taken by purposive sampling technique. The incidence of urolithiasis as the dependent variable, while the amount of intake of drinking, Ca content of drinking water, habit of holding urine, history of hypertension, history of urinary tract infections, consumption of supplements as independent variables. Data were collected through interviews and laboratory tests. Analyzed using univariate and bivariate analysis.The laboratory examination of urine respondents, positive Ca oxalate urine 34 (42.5%) and negative 46 (57.5%). Respondents with a positive urinary Ca oxalate, 51% its drinking water intake is less than 2 liter dilay whereas 24% drinking water intake enough. The bivariate analysis of people who drink less than 2 liters daily at risk of suffering from urolithiasis, p value = 0.035 and PR = 2.112 (95% CI = 1.050 - 4.249). Those who drink less than 2 liters daily at risk for urinary tract stones (urolithiasis). It is recommended for adults to drink at least 2 liters daily to avoid urolithiasis. Keywords : Risk factors, Urolithiasis, Redisari